The mechanical bride: the car as paradigm for house architecture in the sixties - Piantá Costa Cabral, Cláudia (Universidad Nacional de Mar del Plata. Facultad de Arquitectura, Urbanismo y Diseño, 2007)
During the sixties, nomadism and mobility were significant words, addressing changes in the private realm and in domestic scenes. The car, best icon and essential part of fordist economy, meant much more for contemporary culture than simple way of transportation. Through this notion we can understand the highly automobilist pattern of urbanization which emerges with the expansion of fordism in postwar years, and its influence over the architectural field. This paper searches these questions studying a few designs from the sixties, by the Archigram Group, in which the mobile home is the central theme. Remaking the relationship between this work and an enlarged frame, including design, literature, popular culture, we hope to find new readings for Archigram's work and for the sixties.